Three-Phase Hybrid Multi-Output Converter with Single DC and Multi AC Outputs for Hybrid Microgrid Application - Sonkar S.P.; Lal V.N.; Singh R.K. (My University, 2025)
Two multi ac and single dc outputs quasi-Z-source converters (qZSCs) are proposed in this paper. The proposed converters are derived from the quasi-Z-source network by substituting the converter switch to n-numbers of parallel or series-connected 3- inverters. By connecting in parallel mode, the proposed topology yields n-number of ac outputs with the same voltage (switch node voltage (VPN) and variable current (for specific load) with one dc, while topology yields n-number of ac output with the same load current and variable voltage along with one dc by connecting them in series mode. In this topology, constant frequency shoot through (CFST), sinusoidal pulse width modulation (SPWM) technique is used to control the power flow. Multiple load demands can be fulfilled by the proposed converters at a time and they can be applied to the hybrid microgrid and 3- residential ac/dc loads. In this paper, the proposed converters are implemented for two converter units that are capable of delivering two regulated ac and one dc outputs simultaneously at different voltage/current levels. Detailed steady-state, dynamic analysis, and mathematical modeling are carried out to explore the characteristics of the proposed converters. The performance of the proposed converters is validated through experimental results on 380 W prototype. © 2020 IEEE.